2018
DOI: 10.1073/pnas.1716883115
|View full text |Cite
|
Sign up to set email alerts
|

Ethological observations of social behavior in the operating room

Abstract: Operating rooms (ORs) are inhabited by hierarchical, mixed-gender clinical teams that are often prone to conflict. In evolutionary terms, one expects more within- than between-gender rivalries, especially since the OR is a place where all sorts of social interactions occur, not merely technical communications. To document the full range of behavior, the present study used ethological observation techniques, recording live all social behavior by the team. Using an ethogram, 6,348 spontaneous social interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 42 publications
(39 reference statements)
3
51
0
3
Order By: Relevance
“…12 Specifically, cooperation and communication in the OR were observed to decrease when more than half of the healthcare professionals in the room were men, and was strongest when the attending surgeon was also a man. 12 Still, in another recent study, the authors report that women respiratory therapists were challenged more often than men respiratory therapists in a cannot intubate, cannot oxygenate simulation scenario when an incorrect clinical decision was made. 13 There are many psychosocial reasons which may underlie each of these reported observations.…”
Section: Defining Sex and Gendermentioning
confidence: 99%
“…12 Specifically, cooperation and communication in the OR were observed to decrease when more than half of the healthcare professionals in the room were men, and was strongest when the attending surgeon was also a man. 12 Still, in another recent study, the authors report that women respiratory therapists were challenged more often than men respiratory therapists in a cannot intubate, cannot oxygenate simulation scenario when an incorrect clinical decision was made. 13 There are many psychosocial reasons which may underlie each of these reported observations.…”
Section: Defining Sex and Gendermentioning
confidence: 99%
“…For example, Olguín et al (2009) have begun developing and using new technologies, such as wearable badges that record audio, movement and proximity data, to record behaviors and interactions between individuals (Tripathi and Burleson 2012;Curhan and Pentland 2007;Anmol et al 2004;Woolley et al 2010). In addition to wearable badges, data can be collected during observations using hand-held devices and data-coding software (Jones et al 2018;Tejani et al 2010), through video recordings (Jayagopi et al 2009), or extracted from email interactions or collaborative documents (Wise 2014). Using these tools, basic behavioral measures can be collected, such as the timing, duration and directedness of speaking turns, eye gaze, face-to-face interactions, edits to online documents and email exchanges, as well as the timing and duration of team member engagement in teamwork-related tasks.…”
Section: Going Forward: Analyzing the Collective Intelligence Of Teammentioning
confidence: 99%
“…These models could be used to generate predictions for the dynamics of task completion in teams with different team compositions, task demands, and patterns of communication. Predictions could then be compared to the dynamics observed in real teams, using data collected through either traditional observational techniques or more automated means of data collection (Jones et al 2018).…”
Section: Analysis and Modeling Of The Emergence Of Collective Intellimentioning
confidence: 99%
“…Bullying and harassment are known to result in poor mental health, 9 and fear of repercussion limits reporting. 10 Others have shown that cooperation in operating rooms is less common when women are poorly represented on surgical teams, 11 and sexual harassment is more common in environments where women fail to share equally in power. 12 In addition to interventions directly seeking to promote civility in the workplace, a key component to improving workplace culture involves the promotion of women to positions with authority.…”
Section: Preventing the Tower From Toppling For Women In Surgerymentioning
confidence: 99%
“…Similar approaches could be used to improve scientific judgments and decisions throughout the practice of science. Numerous studies indicate that peer review of scientific articles is similarly compromised by biases, as are decisions about hiring, start-up resources, 11 assignment of laboratory space, 12 and hiring advisory board members for biotech companies. 13,14 As a result, even if Jane and John were to receive equal funding, society is less likely to benefit from the cure that Jane's research has the potential to produce.…”
mentioning
confidence: 99%